p53 biology and reactivation for improved therapy in MDS and AML - Joanna E. Zawacka (BMC, 2024)
Abstract Myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) originate from preleukemic hematopoietic conditions, such as clonal hematopoiesis of indeterminate potential (CHIP) or clonal cytopenia of undetermined significance (CCUS) and have variable outcomes despite the successful implementation of targeted therapies. The prognosis differs depending on the molecular subgroup. In patients with TP53 mutations, the most inferior outcomes across independent studies were observed. Myeloid malignancies with TP53 mutations have complex cytogenetics and extensive structural variants. These factors contribute to worse responses to induction therapy, demethylating agents, or venetoclax-based treatments. Survival of patients with biallelic TP53 gene mutations is often less than one year but this depends on the type of treatment applied. It is still controversial whether the allelic state of mutant TP53 impacts the outcomes in patients with AML and high-risk MDS. Further studies are needed to justify estimating TP53 LOH status for better risk assessment. Yet, TP53-mutated MDS, MDS/AML and AML are now classified separately in the International Consensus Classification (ICC). In the clinical setting, the wild-type p53 protein is reactivated pharmacologically by targeting p53/MDM2/MDM4 interactions and mutant p53 reactivation is achieved by refolding the DNA binding domain to wild-type-like conformation or via targeted degradation of the mutated protein. This review discusses our current understanding of p53 biology in MDS and AML and the promises and failures of wild-type and mutant p53 reactivation in the clinical trial setting.